Proposal for the identification of residual stresses after turning and hardening of bearing steel - Šafář, Marek; Valíček, Jan; Harničárová, Marta; Šajgalík, Michal; Tozan, Hakan; Kušnerová, Milena; Drbúl, Mário; Kadnár, Milan; Czán, Andrej (Frontiers in Materials, 2023)
Residual stresses are defined as the stresses that occur in the material without the application of an external load. Their occurrence is related to the technology of production and treatment of the material. This article proposes the identification of residual stresses in a steel material for bearing production, specifically 100Cr6 (1.3505) material. The identification consists in measuring the material by X-ray diffraction method, for which the Proto iXRD mobile diffractometer was chosen. The first measurement was carried out on turned bearing rings and a subsequent second measurement was carried out on the same rings after heat treatment, namely quenching and tempering. This article also proposes a measurement methodology for the bearing rings, where each ring is measured in 6 positions rotated 60° with respect to each other. The measurement results are compared with the individual manufacturing operations, i.e. turning and heat treatment. The results clearly show the expected increase in residual stresses after turning and subsequent decrease after heat treatment. The technological parameters of turning fundamentally influence the residual stresses and thus also affect the quality of the product in subsequent production operations.